HOTS in Reading Activities of Modules 1 to 5 Easy English for Package B - Azizah, Fitria Uswatun; Linggar Bharati, Dwi Anggani (English Education Journal, 2021)
Package B uses a flexible learning principle. The learning process uses a modular learning system. Learning used the latest modules based on the 2013 Curriculum Equivalency Education. This study belongs to qualitative research. The research method is content analysis. This study attempts to analyze the incorporation of analyzing level and evaluating level in reading activities presented in Modules 1-5 Easy English for Package B by referring to Revised Bloom's Taxonomy. The research participants are three English Tutors of Package B. From 168 reading activities, there are 164 LOTS reading activities or 97% and only 4 HOTS reading activities or 3%. The detail is one analyzing reading activity in Module 3, one evaluating level reading activity in Module 1, one evaluating level reading activity in Module 2, and one evaluating level reading activity in Module 3. The knowledge dimensions found in HOTS reading activities are factual and conceptual. The details are a factual knowledge reading activity in Module 1 and three conceptual knowledge reading activities in Module 2 & 3. The result of this study is expected to benefit English tutors to improve or add supplementary materials and reading activities from other sources, the module's author to develop HOTS reading activities in the module, and further researcher to conduct research related to the effectiveness and development of reading activities.